Professional Knowledge “From the Field”: Enacting professional learning in the contexts of practice - Riveros, Augusto; Viczko, Melody (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2012)
Based on a qualitative case study that examined elementary teachers’ understandings of a professional development policy, we question the conceptual disconnection between professional learning and professional practices in some conceptualizations of professional learning communities. We analyse the research data using Actor-Network Theory and report that the teachers in the case study perceived a disconnection between the scenarios of professional knowledge creation and the scenarios of professional practice. Such disconnection is exacerbated due to an ambiguous treatment of the concept of professional practice in the policy documents that endorse the idea of professional learning communities. We conclude that a key element in the transformation of professional practices is the teacher’s awareness that his / her professional knowledge is enacted through his / her actions and practices, thereby concluding that professional learning is situated in the context of professional practices.